Consciousness and cognition - Thau, Michael, 1962- (New York ; Oxford : Oxford University Press, 2002)
Our thinking about consciousness and cognition is dominated by a certain very natural conception. This conception dictates what we take the fundamental questions about consciousness and cognition to be as well as the form that their answers must take. In this book, Michael Thau shows that, despite its naturalness, this conception begins with and depends upon a few fundamental errors. Exorcising these errors requires that we completely reconceive the nature of both consciousness and cognition as well as the fundamental problems each poses. Thau proceeds by discussing three famous and important.
Introduction; 1 SPECTRUM INVERSION; 2 THE STRUCTURE OF BELIEF AND PERCEPTUAL REPRESENTATION; 3 FREGE'S PUZZLE; 4 THE STRUCTURE OF LINGUISTIC COMMUNICATION; 5 BLACK-AND-WHITE MARY; Notes; Works Cited; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Philosophy of mind; Mental representation; Philosophie de l'esprit.; Représentation mentale; PHILOSOPHY -- Mind & Body; Mental representation; Philosophy of mind